Kendala Perbankan Dalam Meningkatkan Kapasitas Koperasi Melalui Pola Joint Financing - Nisabilah Anjani; Tarsisius Murwadji; Bambang Daru Nugroho (Universitas Medan Area, 2020)
This paper aims to develop a joint financing method between banks and cooperatives in which cooperatives in globalization look increasingly lagging behind due to unfinished capital problems and a system that is still traditional at a time of increasingly modern world developments. Therefore, the government made regulations to overcome this problem by creating a Linkage Program. The problem is focused on the cooperative relationship at the Joint financing stage as one of the models of the Linkage program, between South Bandung Farmers Cooperatives with BPR Bandung Kidul. There are various problems in achieving fair and legal cooperation. The method used in this research is normative juridical analysis with descriptive analytical writing methods. This study concludes that the obstacles that hamper the Joint financing relationship, one of which is the ownership of majority shares by cooperatives that can harm the principle of prudence and good corporate governance of the bank. Secondly, in the joint financing relationship between cooperatives and banks in practice no agreements were carried out which could result in business interference by both parties.